2-6(1-x)+x=4(2x-1)-x

Simple and best practice solution for 2-6(1-x)+x=4(2x-1)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-6(1-x)+x=4(2x-1)-x equation:



2-6(1-x)+x=4(2x-1)-x
We move all terms to the left:
2-6(1-x)+x-(4(2x-1)-x)=0
We add all the numbers together, and all the variables
-6(-1x+1)+x-(4(2x-1)-x)+2=0
We add all the numbers together, and all the variables
x-6(-1x+1)-(4(2x-1)-x)+2=0
We multiply parentheses
x+6x-(4(2x-1)-x)-6+2=0
We calculate terms in parentheses: -(4(2x-1)-x), so:
4(2x-1)-x
We add all the numbers together, and all the variables
-1x+4(2x-1)
We multiply parentheses
-1x+8x-4
We add all the numbers together, and all the variables
7x-4
Back to the equation:
-(7x-4)
We add all the numbers together, and all the variables
7x-(7x-4)-4=0
We get rid of parentheses
7x-7x+4-4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

You can always share this solution

See similar equations:

| 17x-3=-43 | | 80-2x=30x= | | (10x+6)(6x+4)=90 | | (a+2)*(a+3)=3 | | -6=(5x-12)/3 | | 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 |

Equations solver categories